Bacterial Infection in Chicken Embryos and Consequences of Yolk Sac Constitution for Embryo Survival. Issue 1 (January 2021) - Rezaee, Mozhgan Sharokhyan; Liebhart, Dieter; Hess, Claudia; Hess, Michael; Paudel, Surya
Bacterial infections in chicken eggs often cause mortality of embryos and clinical consequences in chicks but the pathological mechanism is unclear. We investigated the pathological changes and bacterial growth kinetics in dead and live embryos following infection with 2 Escherichia coli strains with a different clinical background and with 1 Salmonella Enteritidis strain. In 2 experiments, 12-day-old embryos were infected via the allantoic sac with 100 µl of 1 to 5 × 10 2 CFU/ml of one of the bacteria. In experiment 1, only dead embryos were sampled until 4 days postinfection (dpi), and surviving embryos were sampled at 5 dpi. In experiment 2, sampling was performed in dead and killed embryos sequentially at 1, 2, 3, and 4 dpi. The bacteria showed varying pathogenicity in embryos. The yolk sacs of dead embryos showed congestion, inflammation, damaged blood vessels, and abnormal endodermal epithelial cells. Such lesions were absent in the yolk sacs of negative control embryos and in those of embryos that survived infection. The livers and hearts of dead embryos showed congestion and lysed erythrocytes with no morphological changes in hepatocytes or myocardial cells. All bacteria multiplied rapidly in the yolks of infected embryos, although this did not predict survival. However, the livers of dead embryos contained significantly higher bacterial loads than the livers of the embryos that survived infection. The results provide evidence that lesions in the yolk sac, which have been neglected to date, coincide with embryonic mortality, underlining the importance of healthy yolk sacs for embryo survival.